Management of diarrhoea in patients with stable ulcerative colitis with low FODMAP diet, amitriptyline, ondansetron or loperamide: the MODULATE RCT - Lauren A Moreau; Alexander Charles Ford; Matthew James Brookes; Sandra Graca; Elspeth Guthrie; Suzanne Hartley; Lesley Houghton; Karen Kemp; Nicholas A Kennedy; Yvonne McKenzie; Delia Muir; Pei Loo Ow; et al. (Health Technology Assessment)
Background Many patients with ulcerative colitis report ongoing diarrhoea even when their disease is stable and in remission. Design MODULATE was a pragmatic, multicentre, seamless, adaptive, phase 2/3 open-label, parallel-group, multiarm multistage randomised controlled trial. Setting and participants People aged over 18 years with stable ulcerative colitis who had diarrhoea, recruited from secondary care sites in the United Kingdom. Interventions The control arm consisted of modified first-line dietary advice given to all patients with irritable bowel syndrome; the first interventional arm was amitriptyline, a tricyclic antidepressant, which at low doses slows colonic transit; the second intervention was loperamide, an antidiarrhoeal drug also thought to slow colonic transit; the third was ondansetron, an antiemetic thought to slow colonic transit; and the fourth was a diet low in fermentable oligo-, di-, and mono-saccharides and polyols, which is thought to reduce bloating and gas within the small intestine. All patients randomised to an interventional arm were to receive treatment for 6 months. Main outcome measures: Primary outcome measures Phase 2: Improvement in diarrhoea measured using the Gastrointestinal Symptom Rating Scale-irritable bowel syndrome questionnaire at 8 weeks post randomisation: improvement defined as those reporting minor discomfort from diarrhoea or less (scoring ≤ 2 on the diarrhoea subscale). Secondary outcome measures Phases 2 and 3: Measured at both 8 weeks and 6 months: Improvement in diarrhoea measured using the Gastrointestinal Symptom Rating Scale-irritable bowel syndrome. Blood for C-reactive protein, stool for faecal calprotectin at 6 months only, reviewing case notes for escalation of medical therapy for ulcerative colitis. Anxiety and depression, via the Hospital Anxiety and Depression Scale. Results The MODULATE trial opened in December 2021 and closed in January 2023. Of the eight secondary care sites that completed contracting, only four opened to recruitment during this time, and one person was randomised. Trial timelines coincided with the start of the COVID-19 pandemic, causing substantial delays and, ultimately, its early closure. During this time, the trial underwent two major redesign phases, enabling a fully remote participant pathway incorporating electronic consent, remote data capture, posted blood and stool sample kits for eligibility screening, delivery of the dietary intervention via telephone or video call platform, postage of trial investigational medicinal products directly to participants’ homes and all trial follow-up appointments conducted via telephone. The second phase of redesign pushed the trial towards a fully decentralised model. However, this stage was not implemented due to the decision to close the trial early. Limitations The study was unable to recruit the necessary sample size, preventing the trial from progressing. The trial met with several challenges. The Trial Steering Committee’s root cause analysis concluded that the pandemic was the leading factor in trial closure, especially regarding our ability to recruit both sites and participants. Conclusions Although the trial closed early and with insufficient participants to proceed with full statistical analysis, lessons were learnt that could potentially inform future remote trial design and decentralised participant pathways. Future work MODULATE was a commissioned call in response to a priority question identified by people living with ulcerative colitis. The question remains important and unanswered; trials to address it are needed. Given the recruitment difficulties we experienced, consideration should be given to conducting these in both primary and secondary care. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 17/33/03. Plain language summary Ulcerative colitis is a long-term condition, and about one in five people with ulcerative colitis report ongoing diarrhoea. This also causes discomfort and distress, reducing people’s quality of life, and impacting on their psychological health and mood. This is similar to people living with irritable bowel syndrome, who often experience diarrhoea. In irritable bowel syndrome, a diet low in poorly absorbed sugars [known as fermentable oligo-, di-, and mono-saccharides and polyols (FODMAPs)] improves diarrhoea, because some FODMAPs increase small intestinal water content. Drugs like ondansetron (an antisickness drug), amitriptyline (an antidepressant drug) or loperamide (an antidiarrhoeal drug) can also be effective in irritable bowel syndrome with diarrhoea. People aged over 18 years with stable ulcerative colitis who have diarrhoea were eligible to take part. All participants were provided with dietary advice. People were also given one of a low FODMAP diet, ondansetron, amitriptyline, loperamide, or nothing additional. A computer randomly decided who got which one. People were asked to have treatment for 6 months, in addition to their doctor’s usual treatment for ulcerative colitis. People were followed up at 8 weeks and 6 months. Benefits of taking part may have included improvement in symptoms and quality of life, including mood, fewer hospital visits and better-informed decisions regarding the management of diarrhoea in patients with stable ulcerative colitis. Risks were the side effects associated with the drugs (although these were thought to be at a reduced rate due to the low doses used). MODULATE opened to recruitment in December 2021 and closed in January 2023. The team tried to make the trial more convenient for participants to take part by having a remote pathway where all trial activities could be done at home with the support of a researcher on the phone. A second redesign of the trial was planned in an effort to make the trial less burdensome for trial sites and participants. However, this second stage was not implemented. While the trial was open, 17 people were screened, and one person was randomised. Due to the COVID-19 pandemic, the trial struggled to recruit enough participants, and it was decided to close the trial.